Efficient routing strategy of blockchain-based payment channel network - Ru HUO; Dong NI; Hua LU; Yunfeng XIA; Shuo WANG; Tao HUANG; Yunjie LIU (Tongxin xuebao)
In order to solve the problems of the low transaction success rate and network imbalance of the payment channel network, an efficient routing strategy of blockchain-based payment channel network was proposed.This strategy established a dedicated payment channel for the high-priority services according to the service type and service priority, and divided the conventional business into multiple transaction unit.Furthermore, a channel balanced routing algorithm was designed to route each transaction unit, which could reduce the number of transactions on the blockchain and maintain long-term stable operation of the off-chain payment channel, as well as improve the transaction success rate.In addition, in order to avoid the temporary shortage of funds and unavailability of channels due to a certain link occupied by multiple transactions simultaneously, a transaction queuing mechanism in the payment channel network was designed.This mechanism established the forwarding rules for transactions by calculating the escrow amount between the node that transactions arrived and the next hop node, where the channel balanced routing algorithm was used to calculate the new forwarding path for the nodes that could not carry out capital injection within the queuing threshold.The simulation results show that the proposed strategy could improve the transaction success rate and realize the equilibrium of the payment channel network.